Learning Styles of Students Amidst Pandemic Vis-À-Vis Academic Performance in Science 10: A Basis For Proposed Intervention Plan - Ramirez, Maria Agnes P. (Future Science / FSH-PH Publications, 2022)
This research looked upon the learning styles of selected Grade 10 students amidst pandemic vis-à-vis academic performance in science to have a basis for proposed intervention plan to better deliver science instructions for the best teaching and learning experiences where correlations of academic performance and learning styles of the respondents were analyzed. The result shows that majority of the respondents are auditory learners. There are very few kinesthetic learners. Most of the respondents got a Satisfactory level on their academic performance during the first quarter. While there was a noticeable increase in their academic performance during the second quarter where majority of the respondents got Very Satisfactory level. Learning style of the respondents significantly affect their academic performance. This implies that learning style correlates highly to the academic performance. This means that the learning style of the students is connected to their academic performance. Being aware of this, teachers can develop lessons and activities that suits well their learners learning styles. In this way, they are helping their students in developing their skills and increasing their academic performance.